Alkaline Fuel Cell Technology: A Brief Review and Market Size Forecasting - Belrzaeg, Mohamed; A. Masood, Masood (African Journal of Advanced Pure and Applied Sciences, 2022)
With the advent of anionic exchange membrane fuel cells, the world of alkaline-based fuel cells has taken a giant step toward supplanting traditional liquid electrolyte alkaline fuel cells (AFCs). This work aims to introduce and discuss the alkaline fuel cell technology, in addition to discussing all types of fuel cells and the principle of work of each type, and comparing all types. By the end of this work, the global market and forecasting of the alkaline fuel cell was presented, as the growth of this technology is growing globally, which indicates that there will be a clear demand for this the alkaline fuel cell.